The failure of the European Union to offer adequate protection to refugee women - Gwaka, Chiedza (Department of Private Law, 2020)
The majority of refugee and migrant women who are travelling to Europe to seek asylum in the European Union are coming from war-torn countries in order to seek asylum from war or gender-based violence. This is due to the fact that women and children are often targets during war. They may be victims of forced marriages, forced abortions, genital mutilation, genderbased violence, sexual gender-based, rape and murder. Furthermore, these crimes are taking place on refugee routes leading into the European Union and in informal camps within the Union. These informal camps grow rapidly and the refugee populations always outgrow the availability of resources. As a result men and women cannot be housed separately thereby putting women at risk of gender-based violence, sexual harassment and rape. The dilemma therefore faced by refugee women is two-fold; the 1951 Refugee Convention does not mention gender as grounds upon which women can seek asylum meaning women who have suffered persecution and violence on the basis of their womanhood cannot qualify for refugee status and international protection. Secondly, the unsafe conditions of camps and some reception centres in Europe which exposes women to further forms of violence serves to compound their suffering and trauma and also amounts to further violations of their rights. Although EU Member States are aware of these matters, not much practical action has been taken to ensure safety and protection for refugee women.